هاجس المستقبل في الشّعر مبرر وجود - قراءة في قصيدة " مالم تقله زرقاء اليمامة" - بولنوار, بوديسة (جامعة الوادي - University of Eloued, 2020)
الملخص: يتناول البحث قضية المستقبلية في الأدب، مثلما نظّر لها الباحث الجزائري حسين زيداني في أطروحته للدكتوراه: هاجس المستقبل في الأدب، محاولا استقراء نص حداثي هو قصيدة "مالم تقله زرقاء اليمامة" للشّاعر محمد عبد الباري، وتطبيق النّظرة الجديدة على هذا النص، من خلال استخراج المظاهر التي تدلّ هاجس المستقبل، الّذي يعتبر أحد مكوّنات الشعرية الحديثة والتي على أساسها يمكن النظر نظرة حديثة للنصوص الشعرية خصوصا والأدبية بشكل أعم نظرة جديدة، تعيد تصنيف منجزنا الأدبي وتعيد الاعتبار لكثير من النصوص المهمّشة التي تحتوي على هذا الهاجس الذي نعتبره عنصرا أساسيا في الحكم على قيمة النصوص الأدبية، لأنها تضمن للنص الأدبي إعادة إنتاجه وصلاحيته لسياقات تداولية متجدّدة. Abstract: The research deals with the issue of futurity in literature, as the Algerian researcher Hussein Zaidani theorized it in his doctoral thesis: future obsession in literature, trying to extrapolate a modernist text that is the poem of “What the blue dove did not says” by the poet Mohamed Abdel-Bari, and applying the new vision to this text, through extracting the aspects that indicate the obsession of the future, which is one of the components of modern poetry and on the basis of which poetic texts in particular and literary texts in general can be viewed more broadly in a different way, it reclassifies our literary achievement and restores consideration to many of the marginalized texts that contain this obsession, which we consider an essential element in judging the value of literary texts, because it guarantees the literary text’s reproduction and suitability for renewed pragmatic contexts.
مقال
Keywords: هاجس، المستقبل، الشعرية، التداولية، الاستشراف; obsession, future, poetic, pragmatics, foresight.